2017
DOI: 10.1038/s41598-017-09029-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Tribofilm Formation Mechanisms in Ionic Liquid Lubrication

Abstract: Ionic liquids (ILs) have recently been developed as a novel class of lubricant anti-wear (AW) additives, but the formation mechanism of their wear protective tribofilms is not yet well understood. Unlike the conventional metal-containing AW additives that self-react to grow a tribofilm, the metal-free ILs require a supplier of metal cations in the tribofilm growth. The two apparent sources of metal cations are the contact surface and the wear debris, and the latter contains important ‘historical’ interface inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…To check the validity of this assumption, the time is increased into 24 hours, but the film is still not thick enough to be detected by either ATR‐FTIR or EDS. This finding is in agreement with the recent finding by Zhou at al when the formation mechanism of PP tribofilm is studied, and it is found that PP tribofilm formation is unsustainable unless a positive cation is provided from wear debris. This is examined in our tribological work that will be published in due course.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To check the validity of this assumption, the time is increased into 24 hours, but the film is still not thick enough to be detected by either ATR‐FTIR or EDS. This finding is in agreement with the recent finding by Zhou at al when the formation mechanism of PP tribofilm is studied, and it is found that PP tribofilm formation is unsustainable unless a positive cation is provided from wear debris. This is examined in our tribological work that will be published in due course.…”
Section: Discussionsupporting
confidence: 93%
“…In reported literature, a few oil‐miscible phosphonium‐based ILs have been compared with ZDDP. The results showed that oil‐miscible ILs offer superior anti‐wear performance especially at elevated temperature when both had comparable concentrations . The reduction of wear is as a result of the chemical reaction between IL or ZDDP and the interacting surfaces, which lead to form a tribofilm .…”
Section: Introductionmentioning
confidence: 99%
“…[4,[31][32][33] While these nanotribological studies have provided significant insights into IL-mediated lubrication for tribological contacts that involve no chemical reactions between ILs and solid surfaces, studies at the macroscale, which were performed at much higher applied normal pressures and temperatures, provided evidence for the mechano-chemical reaction between IL and metallic surfaces. [34,35] Among the ILs that have been shown to react on solid surfaces under the combined action of normal pressures and shear stresses, phosphonium phosphate ILs (PP-ILs) have been explored extensively due to their good miscibility with hydrocarbon fluids. [36] Qu et al showed that PP-ILs tribochemically react at steel/cast iron sliding interfaces to form surface layers suggested to consist of iron phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, ILs can be used as neat lubricant or lubricant additive in order to decrease friction and wear in various tribological pairs, such as steel-steel, copper-steel, aluminum-steel and steel-composite, among others [1,[9][10][11][12][13][14][15][16]. This is due to the fact that ILs can form tribofilms on the surface of these materials improving their tribological behaviour [17][18][19]. Nevertheless, the ILs commonly used in lubrication present in their composition halogen anions ( and [FAP] -, among others), aromatic cations (imidazolium) and metals (zinc), which can cause negative effects in the environment.…”
Section: Introductionmentioning
confidence: 99%